Rethinking share-of-wallet at the bottom of the pyramid: using financial diaries to observe monthly category trade-offs. Issue 1 (14th January 2019) - Lappeman, James; Chigada, Joel; Pillay, Pragasen
Abstract : Purpose: This study provides empirical evidence for the impact that income and expenditure fluctuations have on understanding the fundamentals of BoP household share-of-wallet in South Africa. Design/methodology/approach: The study used a longitudinal financial diary methodology to record household income in 80 households (in four different geographic areas) over four monthly waves. Findings: The study showed the lack of reliability of aggregated population income and expenditure surveys when understanding the specific behaviour of BoP households. The study concludes that major category trade-offs occur on a monthly basis, and that these trade-offs directly impact our fundamental understanding BoP SoW. Originality/value: While the BoP consumer theory is developing (especially in the last decade), most of the theory is focused on development and business strategy. Empirically based consumer theory is noticeably lacking, given that the BoP is the largest population segment on earth. In addition, research is largely absent of highly rigourous and in-depth quantification of consumer SoW behaviour. This study contributes to the BoP theory by examining monthly fluctuations in income and expenditure, a line of analysis not done before to this extent. In doing so, the study proposes a new metric for the measurement of category expenditure as an index of the total spend.